Payment systems, monetary policy, and the role of the central bank - Johnson, Omotunde E. G. (Washington, D.C. : International Monetary Fund, 1998)
This book reflects the continuing and increasing interest of the IMF in payment system issues, from a public policy perspective. It provides a broad overview of the main policy and strategic issues in payment system reform being addressed by countries around the world. It also describes the structure of various payment systems, particularly those that handle large-value and time critical payments.
Includes bibliographical references (p. 249-254).
oif 21/08/2015
Loans
Keywords: Clearinghouses (Banking).; Banks and banking, Central; Monetary policy; Payment